RESEARCH AND NOISE BY NORMALIZING REGIME IN MACHINE ROOMS COMPRESSOR STATIONS - , О. С. (Municipal economy of cities. Series: «Economy science», 2013)
Analyzed the level of noise in the workplace drivers of technological compressors offer recommendations to reduce them.